Homemade: building the structure of the neurogenic niche - Valamparamban, Ghanim Fajish; Spéder, Pauline (Frontiers in Cell and Developmental Biology, 2023)
Neural stem/progenitor cells live in an intricate cellular environment, the neurogenic niche, which supports their function and enables neurogenesis. The niche is made of a diversity of cell types, including neurons, glia and the vasculature, which are able to signal to and are structurally organised around neural stem/progenitor cells.While the focus has been on how individual cell types signal to and influence the behaviour of neural stem/progenitor cells, very little is actually known on how the niche is assembled during development from multiple cellular origins, and on the role of the resulting topology on these cells. This review proposes to draw a state-of-the art picture of this emerging field of research, with the aim to expose our knowledge on niche architecture and formation from different animal models (mouse, zebrafish and Drosophila). We will span its multiple aspects, from the existence and importance of local, adhesive interactions to the potential emergence of larger-scale topological properties through the careful assembly of diverse cellular and acellular components.